Role of Pradhan Mantri Jan Dhan Yojana in Enhancing the Paradigm of Financial Inclusion in Rural India - Pankaj Gupta; Vaibhav Shrivastava (Integrated Journal for Research in Arts and Humanities, 2022)
This article examines the role of the Prime Minister Jan Dhan Yojana (PM JDY) in boosting public wealth. Millions of households around the country benefit from financial inclusion and banking access, as well as insurance coverage and a sense of security, thanks to this programme. As a result of integrating this scheme with many other government initiatives, money will be immediately credited into the accounts of the recipients, eliminating intermediaries and reducing leakages. This strategy enables access to micro-credit in the later stages of the programme. Many of the accounts created under this plan, however, were idle, a problem that will be addressed once the government links it to other government-run programmes like NAREGA Job Yojna and other direct cash benefit transfer programmes. Overall, this plan has the potential to be a game changer and alter the country's landscape. It might be able to help plug leaks and boost the efficiency of specific public distribution networks. A systematic questionnaire was used to collect primary data, while secondary data was gathered from a variety of sources including books, papers, and published materials. Finally, it makes an effort to propose relevant recommendations to improve PM JDY's standing in terms of increasing public wealth.